Associating metrics of hydrologic variability with benthic macroinvertebrate communities in regulated and unregulated snowmelt‐dominated rivers. (14th September 2017) - Steel, Anna E.; Peek, Ryan A.; Lusardi, Robert A.; Yarnell, Sarah M.
Abstract: Dams and diversions in rivers often alter flow regimes, which in turn can affect stream biota, particularly when the novel conditions are dramatically different from those under which native species evolved. Management of regulated rivers can include development of environmental flows that seek to restore ecological integrity. However, designing a flow regime that adequately supports aquatic biodiversity requires quantifiable metrics of hydrologic variability that directly relate to aquatic species diversity. This study examined both regulated and unregulated montane rivers over 3 years within the marked seasonality of California's Mediterranean climate to determine which quantifiable elements of a flow regime were most correlated with changes in the biologic community, using stream invertebrates during the summer low flow period as an indicator. Boosted regression trees were used to assess relationships between quantifiable metrics of flow regimes and the invertebrate community. Non‐metric multidimensional scaling and a multi‐response permutation procedure were used to analyze general trends in invertebrate assemblage patterns between rivers and years. Results indicated that hydrologic alteration corresponded to differences in invertebrate community composition, and that metrics related to the spring snowmelt recession and variability in summer water temperature had the greatest relative influence on invertebrate community diversity. Rivers exhibiting longer duration spring recessions, lower daily rates of change during the spring recession, and stable water temperatures during summer supported relatively higher invertebrate community diversity. These relationships suggest that quantifiable metrics associated with seasonal flow variability and predictability should be an integral part of environmental flow design and monitoring.